If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 136 + -6x = 3x + 19 Reorder the terms: 136 + -6x = 19 + 3x Solving 136 + -6x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 136 + -6x + -3x = 19 + 3x + -3x Combine like terms: -6x + -3x = -9x 136 + -9x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 136 + -9x = 19 + 0 136 + -9x = 19 Add '-136' to each side of the equation. 136 + -136 + -9x = 19 + -136 Combine like terms: 136 + -136 = 0 0 + -9x = 19 + -136 -9x = 19 + -136 Combine like terms: 19 + -136 = -117 -9x = -117 Divide each side by '-9'. x = 13 Simplifying x = 13
| 183-2x=43x+18 | | 4x=4(9x-2)-3 | | 43-2x=76+16 | | 4xy+6=3w | | 2x+10=42-2x | | 12-10x=81-31x | | -6-6x=9-9x | | 5x+1=2x+3 | | 21.3+a=-37.6 | | 4x+13=83-6x | | 5x+9=119-9x | | 5(6x-2)=28x | | 2x^2=4-7x | | -105-9x=7x+23 | | 5(6x+3)= | | -1x-29=13+2x | | 2x^2-11x=5 | | 5+7x=71+x | | 5x-3=12x-66 | | 2x-5=12x-115 | | 5x+27=12x-36 | | 4x+1=2x+13 | | 5x+40=14x-59 | | 2x+13=58-3x | | 8x-16=5x+5 | | 25+2d=5d+4 | | 3x^3-8x^2-3x=0 | | 3x+35=6x+11 | | 5(y+2)=3y+16 | | 165-5x=5x+15 | | 17-6q=3+q | | 77n^2+14n=0 |